2019
DOI: 10.1038/s41598-019-55040-x
|View full text |Cite|
|
Sign up to set email alerts
|

Evaporation of a sessile droplet on a slope

Abstract: We theoretically examine the drying of a stationary liquid droplet on an inclined surface. Both analytical and numerical approaches are considered, while assuming that the evaporation results from the purely diffusive transport of liquid vapor and that the contact line is a pinned circle. For the purposes of the analytical calculations, we suppose that the effect of gravity relative to the surface tension is weak, i.e. the Bond number (Bo) is small. Then, we express the shape of the drop and the vapor concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…We note that our YLP approach is similar to that used in a very recent study by Timm et al [52] (which was published after our model was developed), who also consider evaporating droplets on an incline. Like our YLP model, they assume the contact line is circular, solve the Young-Laplace equation to determine the shape of the droplet, and compute the flux of liquid at the air/droplet interface by solving Laplace's equation outside the droplet.…”
Section: New Model 2: Young-laplace-popov Modelmentioning
confidence: 96%
“…We note that our YLP approach is similar to that used in a very recent study by Timm et al [52] (which was published after our model was developed), who also consider evaporating droplets on an incline. Like our YLP model, they assume the contact line is circular, solve the Young-Laplace equation to determine the shape of the droplet, and compute the flux of liquid at the air/droplet interface by solving Laplace's equation outside the droplet.…”
Section: New Model 2: Young-laplace-popov Modelmentioning
confidence: 96%
“…On experiments of droplet evaporation on a structured superhydrophobic surface that displays very high contact angle (CA ∼ 160 deg), and negligible CAH (<1 deg) [11]. The droplet evaporation is observed to occur in a constant-contact-angle mode, with contact radius shrinking for almost the entire duration of evaporation [16].…”
Section: Drying Droplets Phenomenon On the Substratementioning
confidence: 99%
“…Drying of droplet is actually a complex, non-equilibrium and difficult-to-control process [8], the control of the deposition morphology of droplet has significant influence. Further studies on this non-uniform redistribution process indicate that inner flows, including capillary flow [9] and Marangoni flow [10], dynamics of the three-phase contact line [11], and particle-particle/particle-interface interaction [12] will influence the final particle distribution.…”
Section: The Study On Dropletsmentioning
confidence: 99%
“…where the depth-averaged radial and azimuthal velocities ūk and vk are given by (26). Equation (30) may be solved by the method of characteristics:…”
Section: The Particle-transport Problemmentioning
confidence: 99%
“…The vast majority of the previous work on deposition from evaporating sessile droplets has, for obvious reasons, focused on axisymmetric deposits from axisymmetric droplets. There has, however, been some work on non-axisymmetric deposits from non-axisymmetric droplets (see, for example, [9,10,[22][23][24][25][26]). In particular, Du and Deegan [23] examined a twodimensional droplet on an inclined substrate numerically, and found that, depending on the initial volume of the droplet and the angle of inclination of the substrate, the larger deposit can occur at either the upper or the lower contact line, while Sáenz et al [25] investigated a variety of non-axisymmetric droplets both experimentally and numerically, and found that larger deposits occur where the contact line has the largest curvature (e.g.…”
Section: Introductionmentioning
confidence: 99%